Expression of Axl in Lung Adenocarcinoma and Correlation with Tumor Progression - Yi-Shing Shinh (Neoplasia: An International Journal for Oncology Research, 2005)
We used the Transwell system to select highly invasive cell lines from minimally invasive parent cells, and we compared gene expression in paired cell lines with high and low invasive potentials. Axl was relatively overexpressed in the highly invasive cell lines when compared with their minimally invasive counterparts. However, there is only limited information about the role of Axl in cancer invasion. The biologic function of Axl in tumor invasion was investigated by overexpression of full-length Axl in minimally invasive cells and by siRNA knockdown of Axl expression in highly invasive cells. Overexpression of Axl in minimally invasive cells increased their invasiveness. siRNA reduced cell invasiveness as Axl was downregulated in highly invasive cells. We further investigated the protein expression of Axl by immunohistochemistry and its correlation with clinicopathologic features. Data from a study of 58 patient specimens showed that Axl immunoreactivity was statistically significant with respect to lymph node status (P < .0001) and the patient's clinical stage (P < .0001). Our results demonstrate that Axl protein kinase seems to play an important role in the invasion and progression of lung cancer.